2019
DOI: 10.1186/s40345-019-0142-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile in patients with newly diagnosed bipolar disorder and their unaffected first-degree relatives

Abstract: Objective The prevalence of metabolic syndrome and insulin resistance is twice as high in patients with bipolar disorder compared with the general population, and possibly associated with a disabling illness trajectory of bipolar disorder, an increased risk of cardiovascular disease and premature death. Despite these detrimental effects, the prevalence of metabolic syndrome and insulin resistance in patients newly diagnosed with bipolar disorder and their unaffected first-degree relatives is large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…MetS is strictly related to incidences of cardiovascular and metabolic diseases, as well as to a reduction of life expectancy, in psychiatric patients. Importantly, an elevated prevalence of MetS and glucose intolerance has been also reported in patients newly diagnosed with BD [42]. Therefore, these conditions should be screened since the early stages to employ prompt and adequate care strategies that can reduce the risk of cardiometabolic complications and premature death, including complementary interventions acting on the lipid profile [43,44].…”
Section: Main Findingsmentioning
confidence: 99%
“…MetS is strictly related to incidences of cardiovascular and metabolic diseases, as well as to a reduction of life expectancy, in psychiatric patients. Importantly, an elevated prevalence of MetS and glucose intolerance has been also reported in patients newly diagnosed with BD [42]. Therefore, these conditions should be screened since the early stages to employ prompt and adequate care strategies that can reduce the risk of cardiometabolic complications and premature death, including complementary interventions acting on the lipid profile [43,44].…”
Section: Main Findingsmentioning
confidence: 99%
“…Regarding the association between physical conditions and MDD, previous studies have concluded that subjects with one or more metabolic disorders had a higher possibility to develop depression [5][6][7]. Therefore, it is necessary to estimate the possible relationship between MetS and MDD for better screening and control of both diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no significant differences seem to exist between schizophrenia and BD patients regarding HDL-cholesterol and triglycerides ( 28 ). Again, these abnormalities may already be present in drug-naïve BD patients ( 62 ). The lipid abnormalities in BD may be state dependent with depression resulting in more anomalous levels than mania ( 63 ).…”
Section: Dyslipidemiamentioning
confidence: 99%